Hematopoietic stem cell transplantation in a patient with type 1 mosaic variegated aneuploidy syndrome - Laberko, Alexandra (Orphanet J Rare Dis, 2019)
BACKGROUND: Mosaic variegated aneuploidy (MVA) syndrome is a chromosomal instability disorder that leads to aneuploidies of different chromosomes in various tissues. Type 1 MVA (MVA1) is caused by mutations in the budding uninhibited by benzimidazoles 1 homolog beta (BUB1B) gene. The main clinical features of MVA1 syndrome are growth and mental retardation, central nervous system anomalies, microcephaly, and predisposition to cancers. There have been no reports of hematopoietic stem cell transplantation (HSCT) in MVA patients. RESULTS: We report an 11-year old boy diagnosed with MVA1 syndrome. The BUB1B gene mutations c.498_505delAAACTTTA and c.1288 + 5G > A were detected using the next generation sequencing (NGS) method. The patient presented with cytopenia soon after birth, but remained stable until 9 years of age, when he developed myelodysplastic syndrome associated with monosomy of chromosome 7. Due to severe dependence on blood transfusions, a TCRαβ+/CD19+ depleted HSCT was performed from a matched unrelated donor (MUD) using a treosulfan-based reduced intensity conditioning (RIC) regimen. The engraftment occurred, and no severe toxicity was observed soon after the HSCT, but on day + 47, graft rejection was detected. It was followed by prolonged pancytopenia and sepsis with multi-organ Enterococcus faecium infection, which led to the patient’s death on day + 156 after HSCT. CONCLUSIONS: In conclusion, we demonstrate that RIC HSCT with TCRαβ+/CD19+ depletion was well tolerated and resulted in complete hematologic recovery in our MVA1 patient, but, unfortunately, it was followed by rapid graft rejection. This fact needs to be taken into consideration for HSCT in other MVA patients.